Leadership Based on Resilience : Lessons from The Donkey Principle by Rachel Anne Ridge - Linda Purnamasari; Youna Cathrine Bachtiar; Noviandi Noviandi (Badan Penerbit STIEPARI Press, 2025)
Authentic leadership has increasingly gained attention in academic studies and organizational practices. The Donkey Principle by Rachel Anne Ridge offers a unique perspective on leadership, emphasizing perseverance, authenticity, and resilience—qualities embodied by the donkey. This article explores the application of these principles in leadership through a literature review methodology, analyzing relevant leadership theories and insights from the book. The findings suggest that effective leaders are not necessarily those who stand out like racehorses, but rather those who remain steadfast in their values, face challenges with resilience, and create long-term meaningful impact. These insights provide valuable contributions to leadership development across various sectors, including business, education, and social organizations.